Pelaksanaan Pemberian Restitusi Bagi Korban Tindak Pidana Perdagangan Orang : Pendekatan Kasus Nomor: 177/Pid.Sus/2021/Pn.Kpg Dan Putusan Pengadilan Tinggi Kupang Nomor: 34/Pid/2022/Pt Kpg - Rezanthi Tiara Labuh; Karolus Kopong Medan; Bhisa Vitus Wihelmus (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Human trafficking is a serious crime that violates human rights and causes physical, psychological, and economic harm to victims. Therefore, the state provides legal protection to victims, one of which is through restitution. This study aims to examine and analyze the implementation of restitution for victims of human trafficking and to identify the obstacles in its enforcement based on Decision Number 177/Pid.Sus/2021/PN.Kpg and Decision Number 34/Pid/2022/PT KPG. This research uses an empirical juridical method with a qualitative approach. Data were collected through interviews with public prosecutors and related parties, as well as literature studies on laws and court decisions. The results show that the implementation of restitution has not been optimal, even though it has been decided by the court. This is caused by several factors, including the inability or unwillingness of offenders to pay restitution, limitations in execution mechanisms by prosecutors as executors, lack of coordination among institutions, and low legal awareness among victims. Thus, the implementation of restitution for victims of human trafficking still faces various obstacles, resulting in the non-fulfillment of victims’ rights optimally. Therefore, stronger regulations, improved roles of law enforcement officials, and more effective implementation mechanisms are needed to ensure the protection and recovery of victims’ rights.